2015
DOI: 10.1007/s12035-015-9324-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Prevents Synaptic Plasticity from VD-Induced Damage via Akt/GSK-3β Pathway and Notch Signaling Pathway in Rats

Abstract: Our previous study has demonstrated that hydrogen sulfide (H2S) attenuates neuronal injury induced by vascular dementia (VD) in rats, but the mechanism is still poorly understood. In this study, we aimed to investigate whether the neuroprotection of H2S was associated with synaptic plasticity and try to interpret the potential underlying mechanisms. Adult male Wistar rats were suffered the ligation of bilateral common carotid arteries. At 24 h after surgery, rats were administered intraperitoneally with sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 43 publications
(65 reference statements)
0
10
1
Order By: Relevance
“…It has also been shown that selective inhibition of NR2A prevents the induction of LTP without affecting LTD production. 35 In the present study, NR2A levels and the NR2A/NR2B ratio decreased in the IS group, whereas there were no significant difference in NR2B level between the IS and CON groups. These findings are consistent with the results of previous studies.…”
Section: Hippocampal Impairmentscontrasting
confidence: 50%
See 1 more Smart Citation
“…It has also been shown that selective inhibition of NR2A prevents the induction of LTP without affecting LTD production. 35 In the present study, NR2A levels and the NR2A/NR2B ratio decreased in the IS group, whereas there were no significant difference in NR2B level between the IS and CON groups. These findings are consistent with the results of previous studies.…”
Section: Hippocampal Impairmentscontrasting
confidence: 50%
“…However, these subunits have different functions; moreover, NR2A is predominantly confined to the synapses of mature neurons, whereas NR2B is mainly distributed extrasynaptically. 34,35 Liu et al 35 showed that the expression of NR2A, but not NR2B, was markedly decreased in the hippocampus in a rat model of vascular dementia, which indicates that weakened synapses and a reduced capacity for neuronal survival are more related to NR2A than NR2B. It has also been shown that selective inhibition of NR2A prevents the induction of LTP without affecting LTD production.…”
Section: Hippocampal Impairmentsmentioning
confidence: 99%
“…After 3 months of treatment, the hippocampus of mouse was separated and stored at -80 °C for the preparation of tissue lysates (n=3). The method of protein extraction was described in our previous studies [30,31]. Each hippocampus was mashed with a grinder and 200 μl lysis buffer (Beyotime Biotechnology, Haimen, China) containing 1% Phenyl methane sulfonyl fluoride (PMSF).…”
Section: Western Blot Assaymentioning
confidence: 99%
“…It was reported that sodium hydrosulfide attenuated neuroinflammation in beta-amyloid(Aβ)-induced AD models by suppressing the expression of proinflammatory factors in the rat hippocampus [18]. In recent studies, H 2 S improved spatial learning and memory abilities in VD, and the underlying mechanism identified in these studies is the Akt-GSK-3β signalling pathway [19]. Epidemiological studies have shown that the most common form of dementia is AD [20], and that the second most common form dementia is VD [21]; however, the current animal models do not mimic the actual pathophysiological process of DACD.…”
Section: Introductionmentioning
confidence: 99%